Love on the Clock: Workplace Romance, Happiness, Fun at Work, and Job Performance among Millennial and Gen Z Employees - Fiona Niska Dinda Nadia; Rasyidi Faiz Akbar (Manunggal Halim Jaya, 2026)
This study investigates the positive role of workplace romance in enhancing job performance among Millennial and Generation Z employees across multi-organizational settings in Indonesia. Using a quantitative approach with 370 respondents who have experienced workplace romance, the research tests a mediation model where workplace happiness and fun at work serve as affective mechanisms linking romance to performance. The findings reveal that, when consensual and well-managed, romantic relationships at work can foster emotional support, engagement, and stronger social bonds, leading to improved job outcomes. The study’s novelty lies in reframing workplace romance—not as a risk factor—but as a potential emotional and motivational resource, particularly within collectivist cultures and younger generational cohorts. It is among the first to empirically demonstrate the dual mediating roles of workplace happiness and fun at work, contributing to both Affective Events Theory and the Broaden-and-Build Theory of Positive Emotions. The study offers theoretical insights and practical implications for organizations navigating relational dynamics in Indonesia’s rapidly evolving workforce.